Use of psychoactive drugs and related falls among older people living in a community in Brazil Uso de medicamentos psicoativos e seu relacionamento com quedas entre idosos - Flávio Chaimowicz; Teresinha de Jesus Xavier Martins Ferreira; Denise Freire Assumpção Miguel (Universidade de São Paulo, 2000)
INTRODUCTION: Population aging in Brazil has increased the prevalence of neurodegenerative diseases (Parkinson's and Alzheimer's disease) and affective disorders (anxiety, depression), all common in old age. A retrospective study was carried out with the purpose of ascertaining if there is an association between falls and psychoactive medication use among older residents of a community in Brazil. METHODS: All residents aged 65+ (n=161) of one neighborhood of Campo Belo, Brazil (population of 48,000) were evaluated regarding the use of psychoactive drugs and the occurrence of falls in the 12 months preceding the study. Vision and hearing screenings were also performed. RESULTS: From the study population, 9.3% were taking prolonged half-life benzodiazepines, 4.4% anticonvulsants (mostly barbiturates), 2.5% antidepressants (all cyclics) and 8.1% alpha-methyldopa. No subject reported use of hypnotics, neuroleptics or drugs to treat Alzheimer's or Parkinson's diseases (except biperiden). As a whole, drugs that increase the risk of falls were used by 1/5 of this population. In the 12-month period preceding the study, 27 residents (16.8%) experienced falls and, of those, 4 (14.8%) had fracture(s). There was an independent association between psychoactive drug use and falls when variables such as age, gender, vision and hearing were controlled (p=0.02). CONCLUSIONS: Although the population of this neighborhood must be considered young (only 4% are 65 years old or more), there are already problems related to the use of psychoactive drugs among people. Prescribed anxiolytics, anticonvulsants, antidepressants and antihypertensives are not appropriate for this age group and their use is associated with falls. INTRODUÇÃO: O envelhecimento populacional no Brasil tem aumentado a prevalência de doenças neurodegenerativas (Parkinson, Alzheimer) e psiquiátricas (depressão, ansiedade), comuns em idosos. Realizou-se estudo retrospectivo com o objetivo de determinar se há associação entre a utilização de medicamentos psicoativos em idosos (65+) residentes na comunidade e a ocorrência de quedas. MÉTODOS: Todos os idosos (n=161) residentes no Bairro Arnaldos (Campo Belo, MG -- 48 mil habitantes), foram avaliados acerca da utilização de psicoativos e da ocorrência de quedas nos 12 meses precedentes e submetidos a exame clínico. RESULTADOS: Benzodiazepínicos de meia-vida longa eram utilizados regularmente por 9,3% dos idosos, anticonvulsivantes (a maioria barbitúricos) por 4,4%, antidepressivos (todos cíclicos) por 2,5% e alfa-metil-dopa por 8%, ou 1/6 daqueles tratando hipertensão arterial. Nenhum idoso utilizava hipnóticos, neurolépticos ou drogas para tratamento de Alzheimer ou Parkinson (exceto biperideno). Em conjunto, drogas que potencialmente podem provocar quedas eram utilizadas regularmente por 1/5 da população. Vinte e sete idosos (17%) informaram ter sofrido queda nos 12 meses que precederam o estudo, quatro ocasionando fratura. A ocorrência de quedas estava associada à utilização de psicoativos (p=0,05), mesmo quando as variáveis gênero, idade, visão e audição foram controladas em uma regressão linear múltipla (p=0,02). CONCLUSÕES: Embora a população do Bairro Arnaldos possa ser considerada jovem (somente 4% tem 65+ anos), já se observam problemas relacionados ao emprego de medicamentos psicoativos em idosos. Os ansiolíticos, antidepressivos, anticonvulsivantes e anti-hipertensivos prescritos são inadequados para esta faixa etária e sua utilização está associada à ocorrência de quedas.